2018
DOI: 10.1158/0008-5472.can-17-3167
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Status ofMETPotentiates Sensitivity to MET and MEK Inhibition in NF1-Related Malignant Peripheral Nerve Sheath Tumors

Abstract: Malignant Peripheral Nerve Sheath Tumors (MPNSTs) are highly resistant sarcomas that occur in up to 13% of individuals with Neurofibromatosis Type 1 (NF1). Genomic analysis of longitudinally collected tumor samples in a case of MPNST disease progression revealed early hemizygous microdeletions in NF1 and TP53, with progressive amplifications of MET, HGF, and EGFR. To examine the role of MET in MPNST progression, we developed mice with enhanced MET expression and Nf1 ablation (Nf1fl/KO;lox-stop-loxMETtg/+;Plp-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…This study revealed the early concomitant presence of MET, HGF, and EGFR amplifications, as well as the site-specific expansion of these loci over time and treatment. These data point to an adaptive mechanism involving RTK signaling for both malignant transformation and clonal selection in MPNSTs [6]. To advance our understanding of the MPNST therapeutic response and resistance to RAS pathway inhibition, we developed diverse preclinical NF1-related MPNST models, including an "MET-addicted" model of NF1-related MPNSTs (NF1-MET), an Nf1/Trp53-deficient model (NF1-P53), and an NF1 model (P53 WT , Hgf -amplified) [7][8][9].…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…This study revealed the early concomitant presence of MET, HGF, and EGFR amplifications, as well as the site-specific expansion of these loci over time and treatment. These data point to an adaptive mechanism involving RTK signaling for both malignant transformation and clonal selection in MPNSTs [6]. To advance our understanding of the MPNST therapeutic response and resistance to RAS pathway inhibition, we developed diverse preclinical NF1-related MPNST models, including an "MET-addicted" model of NF1-related MPNSTs (NF1-MET), an Nf1/Trp53-deficient model (NF1-P53), and an NF1 model (P53 WT , Hgf -amplified) [7][8][9].…”
Section: Introductionmentioning
confidence: 87%
“…Kinome reprogramming can be heavily influenced by genomic alterations (i.e., amplification and mutation) of kinases, the overexpression of other kinases, or ligand activation [13][14][15][16]. Our genomic analysis of MPNST progression identified genomic events during human MPNST progression that heighten RTK signaling, AKT/mTOR activation, and cell survival [6]. To understand how these genomic contexts influence the therapy response to kinase inhibition, we conducted a phosphoproteomic analysis using a reverse phase protein array (RPPA) in our established MPNST mouse models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genomic approaches were recently used to identify the loss of function of polycomb repressor 2 complex components EED or SUZ12 , alongside CDKN2A and NF1 mutations as crucial co-mediators of MPNST transcriptional dysregulation, pathogenesis, and sensitivity to BRD4 inhibitors [9,11] . Others using genomic approaches to explore nerve sheath tumor biology identified MET and HGF amplification in MPNSTs; furthermore, models of MET amplified MPNSTs were subsequently sensitive to the MET inhibitor capmatinib [7] . Transcriptomics-focused approaches have also identified molecular features like MEK signaling, type 1 interferon signaling, and Aurora kinase A as putative therapeutic targets in NF1 tumors [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Others using genomic approaches to explore nerve sheath tumor biology identified MET and HGF amplification in MPNSTs. Furthermore, models of MET-amplified MPNSTs were subsequently sensitive to the MET inhibitor capmatinib [7]. Transcriptomics-focused approaches have also identified molecular features like MEK signaling, type 1 interferon signaling, and Aurora kinase A as putative therapeutic targets in NF1 tumors [12][13][14].…”
Section: Introductionmentioning
confidence: 99%